Frozen Identities: Inter-Ethnic Relations and Economic Development in Penang, Malaysia - Michael Jacobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2009)
Identity formation is probably one of the most discussed aspects of strategic positioning within anthropology, sociology and political science. In general notions of identity have been based on either an absolutist or primordial understanding of belonging or a constructionalist view in which social and political positioning in terms of identity formation are governed by a given societal context. This paper bases its understanding of identity formation on the latter approach. This means that depending of context individuals have several different although related identities to choose between when manoeuvring in a complex and dynamic social environment. Identity formation, achieved or ascribed, and its various forms of externalisation are thus negotiated and not absolute. The dynamic behind this notion of identity formation is individual agency strategically manipulating social, economic and political positioning in a given societal setup. To illustrate the complexities and in this case negative ramifications of social engineering the article focuses on inter-ethnic relations and industrial development in Penang, Malaysia.
hdl:10398/7909
Keywords: 330; Identity formation; Inter-ethnic relations; Industrialisation; Nation building; Penang; Malaysia; Ethnische Beziehungen; Entwicklung; Industrialisierung; Nation; Malaysia